ANALISIS CAMELS DALAM MEMPREDIKSI TINGKAT KESEHATAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2009 – 2011 - Agung Julianto (MEDIA, 2012)
The purpose of this study is to find empirical evidence about differences in the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Profit Margin (NPM), Return on Assets (ROA), Operating Expenses and Operating Income (BOPO), Loan to deposit Ratio (LDR) and Interest Expense Ratio (IER) in accordance with the banks classification (healthy banks and unhealthy banks). Sample was determined using purposive sampling method of 60 listed banks at the Indonesian Stock Exchange (IDX) within period of 2009 through 2011. Approach used in this paper is discriminant analysis. The empirical results show that there were significant differences, CAR with Wilk's Lambda value of 0.927 significant at 0.037 and Wilk's Lambda value of NPL amounted 0.818 and significant at 0.001. This suggests that CAR and NPL can be used to form the discriminant variable. While variable NPM, ROA, LDR and IER shows no significant results, so these variables have a low predictive value in shaping the discriminant variable.